ANALISIS AKUISISI BAHASA PADA PUISI ANAK-ANAK: STUDI KASUS PADA PUISI OLEH ROBERT STEVENSON - PAHOTAN SINAGA (JURNAL ILMIAH SIMANTEK, 2022)
Ray Stevenson's children's poems are one of those poems that have a style and message suitable for children, and many of them are found in children's poetry collections and children's literature books. These poems demonstrate Stevenson's talent for creating works that appeal to young readers. However, although known as a poet, Robert Louis Stevenson's poetry work is not easy to understand and digest by readers, which is because the acquisition of language and words used does not provide a complete understanding of the theme to be described properly, so children do not like the poem presented, where this is due to the acquisition of language and words used do not provide a complete understanding of the theme to be described properly, so that children do not like the poem presented, so that the poem by Robert Louis Stevenson does not get a good response from readers because the meaning presented is not so familiar, so that among children the work of Robert Louis Stevenson gets less attention. The purpose of this study is to understand how children's poetry influences and facilitates the process of language learning in children, as well as how language style and poetry structure help the development of their language skills. This study used a qualitative analysis approach, by collecting children's poems written by Robert Louis Stevenson as research data. The data will be analyzed in depth to identify language styles, poetry structures, and other language elements that influence the process of language acquisition in children. The data collection method is carried out using documentation and observation studies. Based on the results of the study, it can be concluded that Robert Stevenson's poems still cannot attract sympathy and attention for children, where the verses in the poem, the structure of the poem provided, and the complicated language style for children to digest, so that children do not understand the meaning of the poem, resulting in a decrease in children's interest and enthusiasm in using the poem at certain events or certain events.